SARS-CoV-2: Pathogenesis, and Advancements in Diagnostics and Treatment - Khalaf, Khalil; Papp, Natalia; Chou, Jadzia Tin-Tsen; Hana, Doris; Mackiewicz, Andrzej; Kaczmarek, Mariusz (Frontiers in Immunology, 2020)
The emergence and rapid spread of SARS-CoV-2 in December 2019 has brought the world to a standstill. While less pathogenic than the 2002-2003 SARS-CoV, this novel betacoronavirus presents a global threat due to its high transmission rate, ability to invade multiple tissues, and ability to trigger immunological hyperactivation. The identification of the animal reservoir and intermediate host were important steps towards slowing the spread of disease, and its genetic similarity to SARS-CoV has helped to determine pathogenesis and direct treatment strategies. The exponential increase in cases has necessitated fast and reliable testing procedures. Although RT-PCR remains the gold standard, it is a time-consuming procedure, paving the way for newer techniques such as serologic tests and enzyme immunoassays. Various clinical trials using broad antiviral agents in addition to novel medications have produced controversial results; however, the advancement of immunotherapy, particularly monoclonal antibodies and immune modulators is showing great promise in clinical trials. Non-orthodox medications such as anti-malarials have been tested in multiple institutions but definitive conclusions are yet to be made. Adjuvant therapies have also proven to be effective in decreasing mortality in the disease course. While no formal guidelines have been established, the multitude of ongoing clinical trials as a result of unprecedented access to research data brings us closer to halting the SARS-CoV-2 pandemic.